Clinical and Anatomical Aspects of Anterior Dislocation of the Pisiform Bone - Rueff-Barroso, Carlos Romualdo; Delpupo, Fernanda Vieira Botelho; Fazan, Valéria Paula Sassoli; Nascimento, Sérgio Ricardo Rios; Nunes, Lerud Frosi; Montenegro, Rudi Natalli; Kriger, Jorge Luiz; Barroso, Bernardo Garcia (Journal of Morphological Sciences, 2019)
Introduction The pisiform bone is the fourth bone of the proximal row of the carpal bones, and it is located in the tendon of the flexor carpi ulnaris muscle, being considered a sesamoid bone. Traumatic dislocation of the pisiform bone is a rare condition, which usually results from a trauma in dorsal flexion of the wrist. Its treatment can be conservative or surgical, ending or not with the removal of the pisiform bone.Objective To report a case of a child who fell from his own height and presented wrist pain, diagnosed with dislocation of the pisiform bone. We emphasize the importance of anatomy knowledge in the evaluation of wrist trauma.Case Report The anamnesis confirmed that the fall occurred with the wrist in hyperextension. The physical examination showed a slight limitation of movement due to pain. Radiographic exams and a computed tomography (CT) scan of the wrist were performed, in which an anterior deviation/luxation of the pisiform bone was evidenced. A conservative treatment with plaster immobilization for analgesia was performed for 1 week. As there were no symptoms and no signs of trauma consistent with the images, such as edema and local ecchymosis, in addition to the early complete disappearance of pain, the responsible team proposed the hypothesis of asymptomatic chronic dislocation of the pisiform bone.Conclusion Imaging exams in orthopedic traumatology are fundamental for an accurate diagnosis. Nevertheless, they must be associated with knowledge of the anatomy to correlate the image findings with the anamnesis, leading to a better understanding of silent, asymptomatic, and preexisting conditions in the clinical practice.
Keywords: anatomy; pisiform bone; trauma; dislocation